Multiple access interference and multipath interference analysis of orthogonal complementary code‐based ultra‐wideband systems over multipath channels. (7th October 2013) - Bai, Zhiquan; Zhao, Fang; Wang, Changhui; Wang, Cheng‐Xiang
SUMMARY In order to alleviate multiple access interference and multipath interference of ultra‐wideband (UWB) system, we propose the orthogonal complementary code (OCC)‐based direct‐sequence UWB system and offset‐stacking (OS)‐UWB system. OCC has perfect partial autocorrelation and cross‐correlation characteristics. With the application of OCC in UWB system, we can obtain better performance in multiple access interference and multipath interference. The proposed OS‐UWB structure can also achieve variable data rate transmission because of its innovative OS spreading technique. Theoretical analysis and simulation results show that the proposed UWB system can achieve excellent performance and outperform the unitary code‐based direct‐sequence UWB system. Copyright © 2013 John Wiley & Sons, Ltd.